Nursing roles and responsibilities in general practice: three case studies - Walker LA; Clendon J; Nelson K (Royal New Zealand College of General Practitioners, 2015)
INTRODUCTION: Primary care nursing teams may now comprise registered nurses (usually termed practice nurses), nurse practitioners, physician assistants, enrolled nurses, and primary care practice assistants, clinical assistants, or nursing assistants. There is a need to understand how practitioners in the different roles work with patients in the changed environment. The aim of this study was to describe the different configurations of health professionals' skill-mix in three dissimilar primary care practices, their inter- and intra-professional collaboration and communication, and to explore the potential of expanded nursing scopes and roles to improve patient access. METHODS: Document review, observation and interviews with key stakeholders were used to explore how health practitioners in three practice settings work together, including their delegation, substitution, enhancement and innovation in roles and interdisciplinary interactions in providing patient care. A multiphase integrative, qualitative and skill-mix framework analysis was used to compare findings related to nursing skill-mix across case studies. FINDINGS: Three models of primary care provision, utilising different nursing skill-mix and innovations were apparent. These illustrate considerable flexibility and responsiveness to local need and circumstances. CONCLUSION: Enabling nurses to work to the full extent of their scope, along with some adjustments to the models of care, greater multidisciplinary cooperation and coordination could mitigate future workforce shortages and improve patient access to care.
Keywords: General Practice; Humans; Models, Organizational; Nurse's Role; Organizational Case Studies; Patient Care Team; Practice Management, Medical; Primary Care Nursing; Primary Health Care; Socioeconomic Factors; 1110 Nursing; 1117 Public Health and Health Services